Dietary Habits by Income Level during the COVID-19 Pandemic in Indonesia: Results from the IndoNutriLifeCOVID-19 Online Survey - Septiyana, Sorra Milwayani; Aji, Arif Sabta; Reznar, Melissa; Estradé, Michelle; Guo, Isabella; Chin, Yit Siew; Chan, Yoke Mun; Nurwanti, Esti; Rahayu, Herwinda Kusuma; Kurniasari, Yulinda (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) has caused many lifestyle changes, especially in the diet. Policies such as physical distancing and quarantine orders aimed to mitigate to spread of COVID-19 have affected the economy and, therefore, the dietary habits of the people. Aim: The purpose of this study was to analyze the associations between income levels and dietary habits during the COVID-19 pandemic. Methods: This cross-sectional study included 697 Indonesian adults from various regions in Indonesia. The study was conducted from June - August 2020. Data were obtained through a self-administered online questionnaire including dietary habits, lifestyles, and quality of life data adapted from MyNutriLifeCOVID-19 Online Survey. To analyze the associations between income levels and dietary habits during the COVID-19 pandemic, a chi square test was used. Data were analyzed using SPSS version 20. Results: Respondents had mean age of 27.56 ± 8.58 years and the majority were women (83.6%). The percentage of people with large-scale social restrictions was 47.5%. Respondents reported that their dietary habits were healthier during the pandemic (46.2%), with the majority categorized as high and very high-income status (59.1%). From self-reported of the people in Indonesia, there was association between high-income level and self-perceived healthier dietary habits. Higher-income level was also associated with higher frequency of online food/drink delivery, consuming western diet foods, consuming dietary supplements, and probiotic consumption (p<0.05). Conclusions: The self-reported that during the COVID-19 pandemic, the dietary habits of people with a higher income level had healthier compared to their dietary habits before the pandemic. However, it is also related to higher energy, cholesterol, and saturated fat intakes due to consuming high western diet foods. Social inequalities in dietary intake should be considered through promoting a healthy balanced diet with affordable price and healthy food processing in the community.